Assessment of three large-scale depopulation methods for swine - Janice Y. Park; Magnus R. Campler; Ting-Yu Cheng; Brad L. Youngblood; Dawn Torrisi; Michael D. Cressman; Justin D. Kieffer; Todd E. Williams; Andréia G. Arruda; Gary A. Flory; Daniel P. Hougentogler; Jeff Hill; et al. (PLoS ONE, 2025)
The threat of foreign animal disease outbreaks to U.S. swine herds warrants effective and readily available depopulation methods. Current American Veterinary Medical Association-recommendations using preferred physical methods for swine depopulation are unsuitable for large commercial swine herds. Our objectives were to assess and compare the efficacy and performance of three suggested large-scale depopulation methods: 1) medium-expansion water-based foam, 2) prototype high-expansion nitrogen foam and, 3) carbon dioxide gas for finisher pigs under field conditions. Out of 793 finisher pigs included in the study, 84 were implanted with bio-loggers recording electrocardiogram and pig movement data. Aversive pig behaviors were collected manually on a group level for each depopulation method. A subsample of pigs from each method were examined post-mortem for lesions and compared to a reference group of nine pigs euthanized with pentobarbital. Depopulation method assessments included container fill time, the number of aversive pig behaviors observed during depopulation, overall pig movement intensity, time to cessation of movement, time to and cause of cardiac arrest, and respiratory lesions. No difference in fill times between water-based foam and nitrogen foam was observed. The total number of aversive swine behaviors was higher for carbon-dioxide compared to both foam methodologies (P <  0.01). The total pig activity was higher in water-based foam compared to nitrogen foam (P =  0.02) and carbon-dioxide methods (P =  0.01). The mean time to cessation of movement was significantly shorter for water-based foam and nitrogen foam compared to carbon-dioxide (P <  0.01). No differences in cardiac activity were observed. Water-based foam pigs had increased odds of distal trachea occlusions compared to other methods. All depopulation methods demonstrated high efficacy with a 100% mortality rate. The results from this study support large-scale water-based foam, nitrogen foam and carbon dioxide as viable AVMA depopulation guideline candidates for swine.